2006
DOI: 10.1002/jat.1124
|View full text |Cite
|
Sign up to set email alerts
|

The influence of curcumin and manganese complex of curcumin on cadmium-induced oxidative damage and trace elements status in tissues of mice

Abstract: Curcumin (diferuoyl methane) from turmeric is a well-known biologically active compound. It has been shown to ameliorate oxidative stress and it is considered to be a potent cancer chemopreventive agent. In our previous study the antioxidative effects of curcumin in cadmium exposed animals were demonstrated. Also manganese exerts protective effects in experimental cadmium intoxication. The present study examined the ability of the manganese complex of curcumin (Mn-curcumin) and curcumin to protect against oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
25
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 30 publications
(29 reference statements)
6
25
1
Order By: Relevance
“…In the present study the activities of GR and G6PD significantly decreased in the liver tissues of Cd-treated rats. Our findings are in line with previous reports that showed depleted antioxidant activity in Cd-treated rats (49).…”
Section: Discussionsupporting
confidence: 94%
“…In the present study the activities of GR and G6PD significantly decreased in the liver tissues of Cd-treated rats. Our findings are in line with previous reports that showed depleted antioxidant activity in Cd-treated rats (49).…”
Section: Discussionsupporting
confidence: 94%
“…There was a significant decrease in MDA concentration in the curcumin treated samples due to antioxidative effect of curcumin. Our study data is in accordance with the studies of Eybl V et al, [36], Mahfouz MM et al, [37], Manju M et al, [38] showing significant antioxidant effect of curcumin on lipid peroxidation.…”
Section: Discussionsupporting
confidence: 93%
“…This was in agreement with Biswas SK et al, [45], who stated that curcumin can induce glutathione synthesis and increase the level of GSH and glutamylcysteine ligase catalytic subunit mRNA expression in oxidant and TNF α treated cells. The results in this study indicates that, curcumin may have profound effects on cellular redox control and similar to the studies of Eybl V et al, [36] and Sehgal A et al, [46].…”
Section: Discussionsupporting
confidence: 91%
“…Daniel et al (14) reported that CUR chelated Cd and lead in solutions and decreased lipid peroxidation induced by these metals in rat brain homogenate. Curcumin possesses antioxidative and anti-infl ammatory properties, and Eybl et al (15,16) associated it with a drop in Cd content in vivo in rats and mice.…”
mentioning
confidence: 99%